Establishment, evaluation and application of a gas chromatography-mass spectrometry method for quantification of volatile organic compounds in ambient air using anisole as an internal standard - Ivona Sofronievska; Marina Stefova; Jasmina Petreska Stanoeva; Jane Bogdanov (Macedonian Journal of Chemistry and Chemical Engineering)
Gas chromatography coupled with mass spectrometry (GC-MS) is a standard analytical method for identifying specific volatile organic compounds (VOCs) in urban air samples. Quantification ideally relies on calibration curves using standards for each compound. However, due to the variable composition of VOCs and the limited availability of all standards, this strategy is challenging and not always feasible. Quantification using an internal standard is a simple and accurate approach, as it involves the simultaneous analysis of the internal standard and analytes, eliminating the need for a calibration curve if their concentrations fall within the linear dynamic range. In this study, quantification of VOCs from different chemical classes has been evaluated using a single standard mixture and anisole as an internal standard and compared to the external calibration as standard method for quantification by GC-MS. Both methods showed comparable results, with a relative error within ±30% of the theoretical concentration. Linearity was confirmed in the range from 100 to 4000 μg/L, and the relative standard deviation (RSD) of the relative response factors (RRFs) met the acceptance criteria of ≤30% for each target VOC. Toluene, chlorobenzene, C6-C2 and C6-C3 substituted benzenes yielded similar average RRFs, ranging from 1.280 to 1.601 with an RSD of 7.83%. The methods were applied for quantification of VOCs in ambient air on real samples collected on Radiello adsorbents at one urban location. Using anisole as an internal standard proved to be a simple and reliable method for determining VOC concentrations, offering a convenient alternative to external standard calibration.